Thermal Transpiration Flow: Molecular Dynamics Study from Dense to Dilute Gas - Hiroki Yamaguchi; Gota Kikugawa (Fluids, 2023)
Thermal transpiration flow, a flow from cold to hot, driven by a temperature gradient along a wall under a high Knudsen number condition, was studied using the molecular dynamics method with a two-dimensional channel consisting of infinite parallel plates with nanoscale clearance based on our previous study. To accelerate the numerical analysis, a dense gas was employed in our previous study. In this study, the influence of the number density of gas was investigated by varying the height of the channel while keeping the number of molecules to achieve the flow ranging from dense to dilute gas while maintaining a constant Knudsen number. From the flow velocity profile compared to the number density profile, the thermal transpiration flow was observed for all number density conditions from dense to dilute gas. A similar flow structure was exhibited regardless of the number density. Thus, the numerical analysis in a dense gas condition is considered to be valid and useful for analyzing the thermal transpiration flow.